Skills development of technical and vocational education and training (TVET) students: a Letaba TVET College case study, Maake Campus - Thobela, Mmankwana Thomas (University of the Free State, 2025)
Against the backdrop of ongoing national difficulties such as poverty, unemployment, and skills mismatches, this study critically assessed the skills development experiences of students at Letaba TVET College, Maake Campus, South Africa. Significant obstacles persist despite efforts to improve technical and vocational education and training (TVET) outcomes through national initiatives such as the White Paper for Post-School Education and Training and the National Skills Development Strategy (NSDS) III. This qualitative case study used purposive sampling, thematic analysis, and semi-structured interviews to investigate what influences students’ ability to acquire new skills, what they anticipate and encounter throughout their time in school, and how well training programs meet the needs of employers. Findings reveal that severe resource constraints, curriculum misalignment with industry needs, and limited industry-academia collaboration significantly impede effective skills development. Participating students reported a disjunction between theoretical instruction and practical application, leading to inadequate job readiness and reduced employability. Furthermore, external factors such as underfunded institutional support and systemic policy constraints exacerbate these challenges, hindering the capacity of TVET institutions to produce workforce-ready graduates. Although experiential learning and entrepreneurship opportunities were shown to have isolated positive impacts, they were inconsistently implemented, thus failing to systemically transform student outcomes. The study concludes that meaningful improvements require comprehensive reforms, including substantial investment in infrastructure, dynamic curriculum alignment with evolving industry standards, strengthened public-private partnerships, and strategic policy innovations. A proactive integration of technology, enhanced industry exposure through structured internships, and targeted faculty development initiatives are recommended to bridge the gap between education and employment. Addressing these systemic shortcomings is imperative if TVET colleges are to fulfil their potential as catalysts for socio-economic transformation and inclusive development in South Africa. The findings contribute to the growing body of literature advocating for holistic, market-responsive, and inclusive strategies in vocational education reform, particularly within emerging economies navigating the Fourth Industrial Revolution.
Dissertation(MDS (Development Studies))--University of the Free State, 2025
Keywords: Technical and Vocational Education and Training (TVET); Skills development; Employability; Industry-Academia collaboration; Curriculum alignment; South Africa